2019
DOI: 10.1111/jsr.12843
|View full text |Cite
|
Sign up to set email alerts
|

Subjective sleep quality as a mediator in the relationship between pain severity and sustained attention performance in patients with fibromyalgia

Abstract: Pain severity and sleep are associated with cognitive performance in patients with fibromyalgia. This study examined whether sleep mediates the relationships of pain severity with psychomotor vigilance and attention in patients with fibromyalgia by analysing 80 patients with fibromyalgia. Cognitive performance, pain severity and sleep parameters were determined using the Psychomotor Vigilance Task, Brief Pain Inventory–Short Form and sleep diaries of seven consecutive nights, respectively. The patients’ demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Research has shown that sleep disturbance is associated with cognitive difficulties, including impaired executive function and attention, 9 and one study demonstrated that poor sleep mediated the association between pain severity and impaired attentional performance. 8 In the present study, greater sleep disturbance was associated with poorer accuracy for divided attention. Furthermore, we found that sleep disturbance mediated the group difference in divided attention, such that patients with fibromyalgia reported greater sleep disturbance, and in turn, poorer accuracy for divided attention.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Research has shown that sleep disturbance is associated with cognitive difficulties, including impaired executive function and attention, 9 and one study demonstrated that poor sleep mediated the association between pain severity and impaired attentional performance. 8 In the present study, greater sleep disturbance was associated with poorer accuracy for divided attention. Furthermore, we found that sleep disturbance mediated the group difference in divided attention, such that patients with fibromyalgia reported greater sleep disturbance, and in turn, poorer accuracy for divided attention.…”
Section: Discussionsupporting
confidence: 48%
“… 9 , 23 , 24 Interestingly, one study demonstrated that poor sleep accounted for the association between pain severity and impaired attention performance among patients with fibromyalgia. 8 Yet, limited work has explored whether psychosocial factors contribute to differences in cognitive performance that are often observed between patients with fibromyalgia and healthy controls. The present study was a secondary data analysis investigating differences in cognitive performance between patients with fibromyalgia and healthy controls and whether psychosocial factors accounted for these differences.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that two thirds of FM patients have sleep disturbances, but this is not considered an underlying component in its aetiopathogenesis. However, it is accepted that there is a bidirectional relationship in which poor sleep quality leads to increased pain severity and poor cognitive performance in patients with FM [7], clearly constituting a reciprocal relationship [8,9]. Furthermore, this poor sleep quality reported in FM patients, generally assessed only subjectively, leads to worsening symptoms such as depression [10], emotional distress [11][12][13], and difficulties with memory and attention [8,14] that usually develop throughout the course of this disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…Another study that has assessed a model of both sleep and pain in relation to cognition found that in adults with fibromyalgia self-reported sleep quality, but not TST, mediates the association between pain and sustained attention performance, suggesting that improving sleep quality may mitigate the effects of more severe pain on attention. 19 However, this study explored cross-sectional analyses, thus precluding any definitive conclusions regarding temporal cause and effect relationships between sleep, pain, and cognition. We also previously observed that in primarily middle-aged and older adult cardiac patients with implantable cardioverter defibrillators higher sleep efficiency (as assessed by actigraphy) was associated with better attention and processing speed performance, but only in those with more severe pain.…”
Section: Introductionmentioning
confidence: 99%